Variability of Platanus orientalis leaves under a heterogeneous environment in the Hissar Valley of Tajikistan - Davlatzoda Saifiddin; Bobokalonov Jamoliddin; Baikova Elena (BIO Web of Conferences, 2020)
Geospatial monitoring of leaves variability has been performed for Platanus orientalis L. (Platanaceae) in Hissar Valley of Tajikistan. 17 local populations were clustered in four territorial groups and investigated by 11 morphometric variables and four indices. Six levels of variability were taken in the classification of S.A. Mamaev. All tested parameters were ranked due to the total score of variability levels. It was established, that indicators which have the combination of high, increased, and medium levels of variability, can be recommended for the purpose of geospatial monitoring. In the studied set of variables are two such ones: (1) the ratio of the length of leaf blade to the lengh of petiole, and (2) the petiole lengh. These two indicators reliably respond to point sources of industrial environmental pollution (Aluminum and Cement factories). Six indicators with domination of the middle level of variability, are of diagnostic value to differ loci inside territorial groups of populations. The results of the experiment confirmed, that set of variability levels for 8 of 15 studied parameters has diagnostic matter for geospatial monitoring of environment conditions in Hissar Valley of Tajikistan.